2015
DOI: 10.1186/s12985-015-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships of West Nile virus detected in mosquitoes from a migratory bird zone of Colombian Caribbean

Abstract: BackgroundWest Nile virus (WNV) is a member of the genus Flavivirus, and it is transmitted between Culex sp. mosquitoes and avian hosts. Equids and humans are commonly infected with WNV as dead-end hosts, and the signs and symptoms of infection range from mild illness to neurologic symptoms as encephalitis, meningitis and sometimes death. Previous phylogenetic studies have classified WNV into six genetically distinct lineages and provided valuable insight on WNV dispersal patterns within the Americas and its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…We specified a generalized time reversible substitution model following previous WNV studies 11 , 12 , 16 , 22 , 31 , 32 , also including invariant sites and a gamma heterogeneity (GTR + I + G) on our sequences. We set an uncorrelated lognormal relaxed molecular clock 33 following previous studies 11 , 22 , 34 with an initial mutation rate of 0.001 substitutions per site per year and specified a Bayesian Skyline prior 35 .…”
Section: Methodsmentioning
confidence: 99%
“…We specified a generalized time reversible substitution model following previous WNV studies 11 , 12 , 16 , 22 , 31 , 32 , also including invariant sites and a gamma heterogeneity (GTR + I + G) on our sequences. We set an uncorrelated lognormal relaxed molecular clock 33 following previous studies 11 , 22 , 34 with an initial mutation rate of 0.001 substitutions per site per year and specified a Bayesian Skyline prior 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Cx. pipiens mosquitoes are considered the most important vectors in transmitting WNV 43 , 49 , 50 . Entomological surveys conducted after WNV outbreaks in Tunisia showed the abundance and role of Cx.…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia a similar situation was observed where a pathogenic phenotype which exhibited high virulence in Balb/c mice was observed from two WNV isolates from Colombia (COL 524/08, 9835/08) originally obtained from healthy captive American Flamingoes (Phoenicopterus ruber) [ 37 ]. However, two strains recently isolated from mosquito pools in Colombia were reported to be closely related to attenuated strains from Texas [ 38 ]. Although phenotypic characterization of these new Colombian strains has not yet been perform to confirm attenuation, Lopez et al, findings demonstrated the circulation in Colombia of genetic diverse WNV strains [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, two strains recently isolated from mosquito pools in Colombia were reported to be closely related to attenuated strains from Texas [ 38 ]. Although phenotypic characterization of these new Colombian strains has not yet been perform to confirm attenuation, Lopez et al, findings demonstrated the circulation in Colombia of genetic diverse WNV strains [ 38 ]. Thus, it is possible that WNV strains isolated from both the Caribbean and Latin America have variable pathogenic capacities.…”
Section: Discussionmentioning
confidence: 99%